ANALISIS SIX BIG LOSSES PADA MESIN HIGH SPEED BLENDER DI PERUSAHAAN PRODUKSI TEPUNG - Chang, Michael Jordy; Kosasih, Wilson; Ahmad (Jurnal Mitra Teknik Industri, 2023)
This study was conducted in a flour-producing manufacturing company. Based on observation and interview results, the problems faced are engine breakdown and downtime issues on HSB engines and engine components that are rarely replaced so production targets are rarely achieved. This study aims to analyze Total Productive Maintenance by calculating the OEE and the six big losses of the machine, as well as searching for the most critical components of the RPN value using the FMEA method. to find out the biggest damage to the HSB machine. The purpose of this study was to find out the causes of less optimal engine performance and to calculate the machine's efficiency. The average OEE score from September 2021 to August 2022 was 75.79%. With 91.15% availability, performance 87.69% and quality rate 94.85%. Meanwhile, the calculation of the six big losses is known to be the largest loss in reduction speed losses, which has an average rate of 11.52%, Equipment Failure Loss of 4.61%, Set up loss of 4.25%, defect loss of 4.10%, idle and minor stop pages 2.18% and the smallest loss was a reduction of 2.18%. The main priority of improvement is bearing with the highest RPN value of 60.